2018
DOI: 10.1111/codi.14446
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged hospital stay and readmission rate in an enhanced recovery after surgery cohort undergoing colorectal cancer surgery

Abstract: Aim The present database study aimed to identify patients with a longer postoperative length of stay (LOS) or patients readmitted and to characterize both groups based on perioperative factors. Method A retrospective review of the Danish Colorectal Cancer Group database and a local database was performed of all patients undergoing elective resection for colorectal cancer in a 25‐month period. The primary outcome was the number of patients with a prolonged hospital stay (LOS ≥ 10 days after the primary operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
15
2
Order By: Relevance
“…With regards to ASA, Bennedsen et al [17] found that an ASA score ≥ 3 was significantly associated with 30-day readmission in an enhanced recovery after surgery cohort undergoing colorectal surgery, while our data showed no statistically significant association.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…With regards to ASA, Bennedsen et al [17] found that an ASA score ≥ 3 was significantly associated with 30-day readmission in an enhanced recovery after surgery cohort undergoing colorectal surgery, while our data showed no statistically significant association.…”
Section: Discussioncontrasting
confidence: 84%
“…There were some discrepancies among some of the previous publications, and between previously published results and those of the current study, including the influence on readmission of age [2, 11, 12], BMI [1315], gender [16], ASA score [17] or LOS [20, 21]. Randomised studies on beyond-TME surgery should address this aspect in details.…”
Section: Resultsmentioning
confidence: 58%
“…Minimally invasive laparoscopic surgery (Pecorelli et al., 2017) and anorectal approach contribute to a better recovery and a lower risk of readmission and complications severity (Keller et al., 2014; Lawrence et al., 2013; Wood et al., 2018; Yuen et al., 2016). Inversely, stoma creation surgery, rectal surgery, total mesorectal excision and longer surgical procedures are related to a higher risk of emergency room consultation (Wood et al., 2018) and the readmission (Bennedsen et al., 2018; Shah et al., 2017; Wood et al., 2018; Yuen et al., 2016). Abdominoperineal resection of the rectum is associated with several dimension of poor recovery at one month (Jakobsson et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, younger patients may be more stressed at home (Partoune et al., 2017). A high American Society of Anesthesiologists (ASA) score (an indicator of poor physical status) is another characteristic that increases the risk of readmission (Bennedsen et al., 2018; Keller et al., 2014) and postoperative morbidity (Feroci et al., 2013). Even if obesity is associated to a higher ASA score (Chand et al., 2015), only extreme body mass index patients have a higher risk of readmission (Wood et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the mean length of hospital stay was significantly shorter for patients treated using this protocol than for patients treated without the protocol; these results are consistent with those reported by Teixeira et al (19) ,Pisarska et al (20) and Bennedsen et al . (21) in their studies comparing patients who were and were not treated using this protocol. An essential component of most ERAS pathways is multimodal pain management.…”
Section: Discussionmentioning
confidence: 99%